2017
DOI: 10.1021/acs.jpca.7b02577
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Dynamics of H on Graphene by Coadsorbates

Abstract: There are several factors that affect the dynamics of adsorbed hydrogen atoms on a carbon surface. Using density functional calculations we show that coadsorption can be a highly influential factor. The diffusion of hydrogen adsorbed on graphene is explored in the presence of H-containing molecules. Without coadsorbates the diffusion barrier of H on graphene is 0.94 eV, while with water/ammonia it is 0.85/0.12 eV. The low barrier in the case of ammonia is attributed to the formation of a stable intermediate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…[28] The cooperativity or anticooperativity of the interactions was shown to depend on temperature and the direction of approach of the third methane. [32] Wu and Prausnitz, conversely, analyzed experimental data of Henry's constant for alkanes and concluded that for hydrocarbon chains with up to 12 carbons hydrophobic interactions are additive [27] because the hydrophobic potential-defined as the free energy of solvation of the chain with n carbons minus n times the free energy of solvation of methane-was linear with n. Those results are consistent with the finding of Ferguson et al [9] that short alkane chains have the same distribution of conformations in water and vacuum. However, if we compare the projection over R g of the many-body PMF (i.e., the PMF in explicit solvent) and of the linear combination of the two-body PMFs (i.e., the PMF in implicit DP) we would conclude that the contact-pair attraction is anticooperative for the alkanes (polyC) and cooperative for the larger beads (polyM).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…[28] The cooperativity or anticooperativity of the interactions was shown to depend on temperature and the direction of approach of the third methane. [32] Wu and Prausnitz, conversely, analyzed experimental data of Henry's constant for alkanes and concluded that for hydrocarbon chains with up to 12 carbons hydrophobic interactions are additive [27] because the hydrophobic potential-defined as the free energy of solvation of the chain with n carbons minus n times the free energy of solvation of methane-was linear with n. Those results are consistent with the finding of Ferguson et al [9] that short alkane chains have the same distribution of conformations in water and vacuum. However, if we compare the projection over R g of the many-body PMF (i.e., the PMF in explicit solvent) and of the linear combination of the two-body PMFs (i.e., the PMF in implicit DP) we would conclude that the contact-pair attraction is anticooperative for the alkanes (polyC) and cooperative for the larger beads (polyM).…”
Section: Resultssupporting
confidence: 68%
“…The PMF for explicit solvation of C 20 in mW displays the same difference in free energy between compact and extended states as for this same molecule solvated by SPC/E water. [9] Although the barrier-raising for C 20 in mW water is smaller than that observed by Ferguson et al using SPC/E water as solvent, [10] it is within the noise of the calculation with SPC/E water. Consistent with the progression observed for shorter chains in Ref.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…to predict their mobility, diffusion, and dynamics on graphene. [ 115,116 ] Such studies have the potential to lead the way to understanding diffusion barriers and chemical activity of single molecules on graphene for applications in graphene‐based catalysts.…”
Section: Microscopy With a Graphene Substratementioning
confidence: 99%